Analisis Naratife: Perubahan Iklim Dan Dinamika Insiden Demam Berdarah Dengue Di Indonesia - Aziza, Nur; Amir, Rahmi; Nurlinda, Nurlinda; Sudarman, Dirman; Wahyuni Sari, Rasidah (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Climate change is an urgent environmental issue characterized by long-term changes in air temperature, rainfall, and humidity that have a major impact on various aspects of life, including increasing cases of infectious diseases such as dengue fever (DBD). The purpose of this study was to identify the role of climate variables in accelerating the mosquito life cycle and determining the season with an increase in dengue fever cases. The method used is a systematic literature review with a prism 25 google sclora, scienedirect, proquest, journal. The results of the study showed that rainfall is the most dominant climate factor, contributing 84 % to the increase in dengue fever cases because stagnant water becomes a breeding ground for mosquitoes. The optimal temperature of 25-270C accelerates the growth of larvae and replication of the dengue virus while high humidity prolongs the life of mosquites the frequency of disease transmission. Conclusion climate change has a significant impact on the spread of dengue fever. Spkes in cases tend to occur during the rainy season, so mitigation strategies must be adaptive to increasingly unpredictable climate patterns. Preventive efforts such as improving climate monitoring systems are needed